ANALISA EFISIENSI KINERJA CRUSHER PADA PRODUKSIPENCACAHAN PLASTIK STUDI KASUS PT. HANGLEKIU PLASTIK ABADI - Dimas Mei Aldhi (2023)
Productivity is a measure of efficiency in producing output. Inputs are often limited by labor factors, while outputs are measured in various forms such as physical, form or value. Efficiency is defined as the best comparison between input (input) and output (output). In the process of making chopped plastic there is an enumeration process with plastic raw materials, this enumeration stage is very important in the production process in the next production process. In this study, the method of calculating the value of the availability of tools using the PAM (Process Activity Mapping) approach was used to describe activities that are value added and non value added. PT Hanglekiu Plastik Abadi needs to pay attention to the efficiency value of the availability of crusher work tools contained in its production line. The purpose of this research is to determine the work efficiency of the crusher before and after analyzing the availability of crusher work tools and to provide suggestions for increasing the work efficiency of the crusher at PT Hanglekiu Plastik Abadi. Based on the results of data processing and analysis, it was found that the work efficiency of the PT Hanglekiu Plastik Abadi crusher before the repair was the Mechanical Availability value of 92.92%, Use of Availability 88.43%, Effective Utilization 84.35%, but after the repair there was an increase in the Mechanical Availability value 97.00%, Use of Availability 95.14%, Effective Utilization 93.35%.